The wettability characteristics of DLC coating for tribological engineering applications - Sulaiman, Mohd Hafis; R.N., Farahana; L, Tajul; H, Jaafar (IOP, 2019)
Hard coating deposited to tool steel surface can greatly improve wear resistance and reduce sticking. Since solid-liquid interactions are present in every lubricated tribological contact, the present study is aimed to understand the physical phenomena of contact interactions between the DLC coated surface and the liquid. In this study, double-layer DLC/TiAlN coating was prepared via Physical Vapour Deposition (PVD) process. The anti-sticking properties were assessed using contact angle measurements using two liquids with distinctly different viscosity – water and oil. No significant differences found in the contact angle values for both liquid properties. The results revealed that the DLC/TiAlN coated tool steel surfaces exhibit hydrophobic behaviour with high contact angle values. With a lower surface energy of the DLC/TiAlN coating in comparison to uncoated surface, this suggests that the DLC/TiAlN coating is a good hard coating candidate since it has a lower adhesion resistance and an improved release performance.